Understanding Online Buying Behavior in University Students: The Role of Conformity and Academic Stress on Compulsive Buying - Ahmad, Favian; Untoro, Vinaya; Wiroko, Endro Puspo (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Shopping, especially online shopping, has become common for university students. Online shopping behavior is often caused by the interest in advancing social status and getting rid of negative feelings that someone is experiencing. Unconsciously, if done repeatedly, this behavior can lead to compulsive buying. This study aimed to determine the role of conformity and academic stress on compulsive buying in online shopping among university students. This quantitative study, with convenient sampling to collect data. Respondents in this research involved 200 students aged 18-25 as the study sample. Regression analysis was executed by using SPSS. This study's results show a significant role of conformity and academic stress in compulsive buying among university students. Conformity significantly contributes to compulsive buying with a contribution of 15.1%, and academic stress can trigger compulsive online shopping behavior among university students with a contribution of 29%. Based on this research, university students need to understand their conformity related to their peers so they will not be impacted by compulsive buying. Moreover, university students also need to manage their stress levels associated with the academic environment so that they will not be impacted by compulsive buying.Berbelanja khususnya berbelanja online sudah menjadi hal yang biasa bagi kalangan mahasiswa. Perilaku berbelanja online sering disebabkan oleh kepentingan dalam mengedepankan status sosial dan menghilangkan perasaan negatif yang sedang dirasakan seseorang. Tanpa disadari hal tersebut jika dilakukan secara terus berulang dapat menimbulkan perilaku compulsive buying. Tujuan penelitian ini adalah untuk mengetahui peran konfomitas dan stres akademik terhadap compulsive buying dalam belanja online pada mahasiswa. Penelitian ini adalah penelitian kuantitatif, dengan pengambilan responden menggunakan convenient sampling. Subjek pada penelitian ini adalah 200 mahasiswa berusia 18-25 tahun. Analisis data menggunakan uji regresi menunjukkan bahwa terdapat peran signifikan konformitas dan stres akademik terhadap compulsive buying belanja online pada mahasiswa. Konformitas berperan signifikan terhadap compulsive buying dengan sumbangan sebesar 15,1% dan stres akademik mampu berperan dalam memunculkan compulsive buying belanja online pada mahasiswa dengan sumbangan sebesar 29%. Berdasarkan penelitian ini, mahasiswa perlu memahami konformitas dirinya dengan rekan sebayanya agar tidak terdampak compulsive buying. Selain itu, mahasiswa juga perlu mengelola stress yang berhubungan dengan lingkungan akademik agar tidak terdampak compulsive buying.